Communication With Staff During Hospitalization for Childbirth: The Patient's Perspective [1R]. (May 2016) - El Haj Ibrahim, Samia; McCulloch, Jeanette; Korst, Lisa M.; Fridman, Moshe; Fink, Arlene; Gregory, Kimberly D.
Abstract : INTRODUCTION: Hospital Consumer Assessment of Healthcare Providers and Systems (HCAHPS) survey scores impact hospital reimbursement. Patient-provider communication is a key driver of these scores. We explored the role of communication in childbirth hospital admissions from the pregnant woman's perspective. METHODS: We performed a systematic and comprehensive literature search regarding patient-reported outcomes (PROs) in childbirth, organized them into categories, and mapped them to a conceptual framework. In collaboration with a community partnership of clinicians and childbirth advocates, we held focus group sessions among pregnant and recently pregnant women from different racial/ethnic and socio-economic populations in Los Angeles County to determine women's priorities among these categories. Sessions utilized a standardized script for facilitators and were recorded, transcribed, and translated as needed. Using ATLAS.ti, responses were organized into themes and mapped to the categories. RESULTS: Nineteen categories of PROs were identified, including clinical outcomes and processes of care, eg, labor and pain management, and patient-provider communication. For the 6 focus groups (N=41), communication was the most prevalent theme identified, and related concerns were associated with negative childbirth experiences. Among Spanish speakers, concerns included not being understood, and translator availability. African-American women acknowledged being understood; however, they felt ignored and placated. Medicaid-insured women voiced a lack of privacy when communicating with providers. CONCLUSION: Communication with hospital staff was the principal concern during childbirth for a diverse sample of women; these concerns varied by race/ethnicity and insurance status. As maternity patients contribute to HCAHPS scores, strategies for addressing these concerns are critical for childbirth hospitals.